Institutional dilemma: Quad and ASEAN in the Indo-Pacific - Koga, Kei (2023)
How is the future of the Indo-Pacific institutional arrangements envisioned by the Quad and ASEAN? Are they mutually exclusive or compatible? How can the institutional competition between the Quad and ASEAN in the Indo-Pacific be avoided? I argue that the institutional competition between the Quad and ASEAN can be provisionally alleviated through strategic ambiguities about the institutional division of labor in the Indo-Pacific. However, such strategic ambiguities do not resolve normative inconsistencies between the Quad and ASEAN, which would probably trigger institutional competition in the future. To resolve such difficulties, both the Quad and ASEAN need to create a mechanism that clarifies their regional institutional division of labor.